Real-time in situ monitoring via europium emission of the photo-release of antitumor cisplatin from a Eu–Pt complex1. Issue 74 (25th September 2015) - Li, Hongguang; Lan, Rongfeng; Chan, Chi-Fai; Jiang, Lijun; Dai, Lixiong; Kwong, Daniel W. J.; Lam, Michael Hon-Wah; Wong, Ka-Leung
<x xml:space="preserve">Abstract</x> A light-responsive antitumor agent, PtEuL, has been synthesized and evaluated for controlled cisplatin release by linear/two-photon excitation in vitro with concomitant turn-on Eu emission as a responsive traceable signal.